2004
DOI: 10.1158/1078-0432.ccr-04-0448
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of p16 Protein Levels in Oropharyngeal Squamous Cell Cancer

Abstract: Purpose: Functional inactivation of p16 is an early and frequent event in head and neck squamous cell cancers. In this study, we sought to determine whether p16 expression is of prognostic importance in oropharyngeal squamous cell carcinoma.Experimental Design: p16 protein expression was evaluated by immunohistochemistry in a tissue microarray composed of 123 oropharyngeal squamous cell cancers with a mean patient follow-up time of 33 months.Results: p16 overexpression was associated with more advanced Tumor-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
103
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 44 publications
11
103
1
3
Order By: Relevance
“…Interestingly, we found no correlation between p16 protein expression and outcome. In contrast to studies of p16 mRNA, previous studies have reported overexpression of p16 protein to be predictive of improved prognosis in oropharyngeal squamous-cell cancer (Weinberger et al, 2004), vulvar carcinoma (Knopp et al, 2004) and colorectal carcinoma (Zhao et al, 2003;Cui et al, 2004), whereas high levels of p16 protein expression have been associated with shorter event-free survival in prostate cancer (Lee et al, 1999). Whether these inconsistencies reflect tumourspecific roles of p16, or differences in the prognostic significance of mRNA and protein remain to be seen.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, we found no correlation between p16 protein expression and outcome. In contrast to studies of p16 mRNA, previous studies have reported overexpression of p16 protein to be predictive of improved prognosis in oropharyngeal squamous-cell cancer (Weinberger et al, 2004), vulvar carcinoma (Knopp et al, 2004) and colorectal carcinoma (Zhao et al, 2003;Cui et al, 2004), whereas high levels of p16 protein expression have been associated with shorter event-free survival in prostate cancer (Lee et al, 1999). Whether these inconsistencies reflect tumourspecific roles of p16, or differences in the prognostic significance of mRNA and protein remain to be seen.…”
Section: Discussionmentioning
confidence: 90%
“…This has been independent of treatment modality, either primary chemoradiation, induction chemotherapy followed by definitive radiotherapy, or primary surgery with or without postoperative chemo radiotherapy [2,5,9,12,19,20]. Hazard ratios for overall, progressionfree, disease-free, and disease-specific survival for p16 positive versus negative cases are consistently low (Table 2) [2,3,5,6,12,21]. Also, all major studies that performed multivariate survival analysis to control for other variables have found that positive p16 IHC independently correlates with better survival [2,5,6,9,12].…”
Section: Introductionmentioning
confidence: 93%
“…Several studies have consistently shown HPV infection and p16 immunoexpression to be independent favorable prognostic factors in head and neck cancers, especially among the oropharyngeal cancers (Begum et al, 2003;Weinberger et al, 2004;Reimers et al, 2007;Ang et al, 2010). Some studies have shown no prognostic relevance pertaining to loss of p16 expression (Geisler et al, 2002).…”
Section: Introductionmentioning
confidence: 99%